Combinative solution processing and Li doping approach to develop p-type NiO thin films with enchanced electrical properties - Oluwabi, Abayomi T.; Spalatu, Nicolae; Maticiuc, Natalia; Katerski, Atanas; Mere, Arvo; Krunks, Malle; Acik, Ilona Oja (Frontiers in Materials, 2023)
The deposition of nickel oxide (NiOx) thin film from an acetylacetonate source has been avoided by many solution-based techniques owing to poor solubility in alcohol solvents. From this perspective, this work provides a systematic investigation on the development of NiOx thin film using a combinative approach of ultrasonic spray pyrolysis (USP) and Li dopant for synthesis and optimization of structural and optoelectronic properties of the films. An in-depth comparative analysis of nickel acetylacetonate based precursor employing acetonitrile and methanol as solvents is provided. It is demonstrated that USP from acetylacetonate precursor yielded uniform, well-compact, and transparent films, with polycrystalline cubic NiOx crystal structure. By screening the deposition temperature in the range of 300-450 oC, 400 oC was identified as an optimal processing temperature leading to uniform, compact, highly transparent and p-type conductive films. At optimized deposition condition (400 oC), lithium doped NiOx (Li:NiOx) thin film was deposited. The shift of the main (200) XRD peak position from 43.48° (0-Li:NiOx) to 43.56° (60-Li:NiOx) indicates the Li incorporation into the NiOx lattice. X-ray photoelectron spectroscopy (XPS) study was employed to unravel the incorporation of Li into the deposited Li:NiOx thin films. With the deconvolution of the Ni 2p core level for the as deposited (0, 60)-Li:NiOx films, the intensity of Ni3+ related peak was found to increase slightly with Li doping. Furthermore, all the deposited Li:NiOx thin films show p-type conductivity behaviour and the resistivity was reduced from 104 Ωcm (0-Li:NiOx) to 102 Ωcm (60-Li:NiOx). Based on these results, the deposited NiOx and Li:NiOx thin films suggested that USP-deposited Li:NiOx is highly suitable for its application in inverted structure solar cell as the hole transport layer.